Spatiotemporal variation in grain production performance and efficiency of the cultivated landscapes in Upper Blue Nile Basin of Ethiopia: the impact of residual moisture-based farming on water and food security - Kassawmar, Tibebu; Teferi, Ermias; Tsegaye, Samson; Bewket, Woldeamlak; Zeleke, Gete; Abraha, Lemlem; Walsh, Claire L.; O’Donnell, Greg (Frontiers in Sustainable Food Systems, 2024)
Analysis of grain production performance can provide reference information to explore multiple cropping options and further improve the resource use efficiency of farming methods. This study investigated the spatiotemporal dynamics of grain production performance and efficiency of major crop production systems (CPS) in the Ethiop's Blue Nile Basin. The results show that only 39% of the basin is currently cultivated, although a significant cropland expansion (10%) was recorded between 1985 and 2020. The study identified 11 major CPS, mostly practiced in the basin. Of these, single cropping based on the main rainy season (Meher-Only) covers the largest area (26%), followed by Meher-Residual-Intermittent (12%) and Meher-Belg-Dependable (11%). Extended-Meher, Meher-Residual-Dependable and Meher-Residual-Intermittent and Meher-Belg-Dependable are the four more powerful CPS with higher efficiency. Comparatively, CPS practiced in Wet-Woyna-Dega and Wet-Dega have better overall performance. Findings confirm that agricultural-space management (land) and green-water(rainfall) utilization are the most influential factors, followed by land use planning and land use systems (CPS) invention. As landscape suitability for grain production govern future performance, in the low elevation and flood plains parts of the basin, the possibility of creating additional space into the food system is very high. In mountainous and high-altitude regions, the efficiency of grain production will decrease because incorporating additional arable land into the food system is trivial. In the last three decades, in BNB, only 10% of arable land(equivalent to 30 million quintal of food) have been added in the good system, which can support about 6 million people. Compared to the population growth of the basin (12 million 1985-2020), its contribution to the food system was less than 50%. This confirms multiple cropping systems such as Residual moisture based CPS, have played a significant role in boosting food system in the basin. Therefore, improving the grain production performance/efficiency requires targeted investments, including the invention of more adaptable crop varieties, efficient cropping practices, the introduction of advanced agricultural space and water management technologies. The results of the study will help identify important policy gaps and suggest possible options to enhance residual farming and other multiple cropping systems.